Optimal intervention: Flexible Fiberoptic Bronchoscopy’s Role in Chronic Aspiration Foreign Body Removal - Zulfikar, Teuku; Akbar, Syarial; Arnanda, Rifian (Indonesian Journal of Case Reports, 2023)
Foreign body aspiration in the lower airway is prevalent among children under 5 years old and rare among adults, except in cases of neurodegenerative or neuromuscular conditions. This condition is linked to substantial morbidity, necessitating awareness of potential complications. Flexible bronchoscopy stands as a primary method for foreign body removal. We present a case of a 56-year-old male who aspirated a denture 15 years ago. Recent symptoms encompassed persistent hemoptysis, worsening over two weeks, accompanied by mucopurulent sputum, fever, chest pain, and dyspnea. Physical examination indicated shortness of breath with positive rhonchi. X-ray revealed tubular opacities and atelectasis. Two days post-admission, flexible bronchoscopy exposed moderate mucopurulent secretion in both bronchial trees, with multifocal hyperemic edematous mucosal changes in the right bronchial tree. A denture was successfully extracted from the lower left lobe during the procedure. Treatment included antibiotics, bronchodilators, and mucolytics. Flexible fiberoptic bronchoscopy's adaptability allows local anesthesia usage, reducing costs and risks. The integration of high-definition imaging in flexible bronchoscopes enhances airway visualization and foreign body localization, ensuring precise and safe removal.